IMPACT OF THE USE OF ENHANCED LEARNING EXERCISES ON THE LEARNING OF CERTAIN SKILLS BY PLAYERS' LOUNGE FOOTBALL - Farah falah hassan Muhammed (Proximus Journal Publishing, 2024)
The aim of the research is to recognize the impact of the enhanced learning method on learning some skills with a lounge football. To recognize the statistical differences between the experimental group and the control in learning some skills with a distance test lounge football, the researcher used the experimental curriculum to suit the research's problem and objectives. In 2024, the research community included the 52-player specialized lounge football school at the Iraqi Ministry of Youth and Sports. The sample of the research was selected in a regular random manner, which amounted to 40 female players distributed to the pilot and control groups equally and 20 female players per group The researcher then conducted coherence and parity transactions for the two research groups, and then the modules were prepared according to the enhanced learning model. The curriculum followed by the two research groups was implemented. Enhanced learning exercises were used with the experimental group and the method used by the teacher with the control group. School of Sports Education, University of Babylon, with the supervision of the researcher. The vocabulary of the curriculum: the total curriculum lasted 9 weeks
Keywords: school; curriculum; Sports